Long-term outcomes of slipped capital femoral epiphysis treated with in situ pinning - de Poorter, Jolanda J. (J Child Orthop, 2016)
PURPOSE: Slipped capital femoral epiphysis (SCFE) is the commonest hip disorder in adolescents. In situ pinning is commonly performed, yet lately there has been an increase in procedures with open reduction and internal fixation. These procedures, however, are technically demanding with relatively high complication rates and unknown long-term outcomes. Nevertheless, reports on long-term results of in situ fixation are not equivocal. This study evaluates the possible higher risk of worse outcome after in situ pinning of SCFE. METHODS: All patients treated for SCFE with in situ fixation between 1980 and 2002 in four different hospitals were asked to participate. Patients were divided into three groups, based on severity of the slip. Patients were invited to the outpatient clinic for physical examination and X-rays, and to fill out the questionnaires HOOS, EQ5D, and SF36. ANOVA and chi-squared tests were used to analyze differences between groups. RESULTS: Sixty-one patients with 78 slips filled out the questionnaires. Patients with severe slips had worse scores on HOOS, EQ5D, and SF36. 75 % of patients with severe slips had severe osteoarthritis, compared to 2 % of mild and 11 % of moderate slips. CONCLUSION: Hips with mild and moderate SCFE generally had good functional and radiological outcome at a mean follow-up of 18 years, and for these hips there seems to be no indication for open procedures. However, severe slips have a significantly worse outcome, and open reduction and internal fixation could therefore be considered.